2013
DOI: 10.1002/elps.201200292
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic viability of Escherichia coli trapped by dielectrophoresis in microfluidics

Abstract: The spatial and temporal control of biological species is essential in complex microfluidic biosystems. In addition, if the biological species is a cell, microfluidic handling must ensure that the cell's metabolic viability is maintained. The use of DEP for cell manipulation in microfluidics has many advantages because it is remote and fast, and the voltages required for cell trapping scale well with miniaturization. In this paper, the conditions for bacterial cell (Escherichia coli) trapping using a quadrupol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…Previous studies showed that the electric field could induce damage to yeast cells or bacteria with a long time AC field application [28,41]. For example, the number of viable yeast cells was reduced by 56.8% to 89.7% with a DEP treatment longer than 4 h [28], and trapping of genetically-modified E. coli was only workable for an AC field application of less than 10 min [41]. These results demonstrate the importance of the careful selection of the AC field duration to avoid damage of cell membrane integrity.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that the electric field could induce damage to yeast cells or bacteria with a long time AC field application [28,41]. For example, the number of viable yeast cells was reduced by 56.8% to 89.7% with a DEP treatment longer than 4 h [28], and trapping of genetically-modified E. coli was only workable for an AC field application of less than 10 min [41]. These results demonstrate the importance of the careful selection of the AC field duration to avoid damage of cell membrane integrity.…”
Section: Resultsmentioning
confidence: 99%
“…Since the first report of the microfabrication technique for DEP devices in 1988, the 1990s saw an explosion of implementing DEP experiments with metal microelectrodes. The microelectrodes commonly used are carbon and metals, such as gold , platinum , titanium or silicon , among which gold and platinum electrodes are ideal choices due to the stable electrochemical property.…”
Section: Configurations Of Electrodes and Dep Devicesmentioning
confidence: 99%
“…In Donato S’s experiment, cells were trapped under the pDEP for a period of time. The result indicates that the cell metabolism is affected by the electric field after 10 min of exposure, while the cells no longer produce GFP after 15 min of exposure, and most of the cells died [127]. Therefore, for bioparticles, the exposure time in the electric field must be controlled.…”
Section: The Effect Of Dielectrophoresis On Bioparticle Viabilitymentioning
confidence: 99%